An investigation of creativity and conceptual understanding in state of matter using directed creative process based science project among year 5 primary school students - Yong, Ching Syuen (2013)
The growing interest and concern about creativity elements in our education system has prompted much research been done on creativity assessment. This research explores the application of directed creative process in primary science project as an instructional strategy for fostering and assessing creativity and conceptual understanding of State of Matter in science subject among primary school students. The respondents consist of 32 students from a Chinese Primary School located in Tenom, Sabah. This research employed experimental design research where the data was analysed quantitatively. A single pre test-post test group was given an intervention of directed creative process based science project during their science lesson in duration of three weeks. There are two instruments used in this study, namely pre-test and post-test of science conceptual understanding test and Torrance's Figural test of Creative Thinking (TTCT) adapted from Torrance (1966). Five dimensions of creative thinking skills among students which comprise of Fluency, Originality, Elaboration, Abstractness of Title and Resistance to Premature Closure were evaluated based on TTCT test. The data obtained were anaylised by using Statistical Package for the Social Science (SPSS) 16.0 for Paired-sample t-test while the percentages of students in different category of creativity levels were computed in Microsoft Excel. The research finding revealed that there was positive effect of the intervention, as there were significant difference in mean scores between pre-test and post test in conceptual understanding in science (P= 0.000) as well as in mean score between TTCT pretest and post-test total scores (P=0.000) while there were significant difference in mean scores between pre test and post test in the "Elaboration:, "abstractness of title" and "Resistance to Premature Closure" dimensions of TCTT test, however, the results reveal that there is no significant difference in mean score between pre-test and post-test in the "Fluency" and "Originality" dimension of TTCT Test. At the end of the intervention, it was found that majority of the students (62.50%) have a moderate level of creative thinking and the rest of them were found creative (31.25%) and less creative (6.25%). The study recommends the application of directed creative process in project-based learning model for repeated uses on any educational institution especially primary and secondary schools to enhance students' creative thinking skills and conceptual understanding in their learning.